Effect and mechanisms of exercise for complex regional pain syndrome - Li, Tian-Shu; Wang, Rui; Su, Xuan; Wang, Xue-Qiang (Frontiers in Molecular Neuroscience, 2023)
Complex regional pain syndrome characterized by severe pain and dysfunction seriously affects patients’ quality of life. Exercise therapy is gaining attention because it can effectively relieve pain and improve physical function. Based on the previous studies, this article summarized the effectiveness and underlying mechanisms of exercise interventions for complex regional pain syndrome, and described the gradual multistage exercise program. Exercises suitable for patients with complex regional pain syndrome mainly include graded motor imagery, mirror therapy, progressive stress loading training, and progressive aerobic training. In general, exercise training for patients with complex regional pain syndrome not only alleviates pain but also improves physical function and positive mental status. The underlying mechanisms of exercise interventions for complex regional pain syndrome include the remodeling of abnormal central and peripheral nervous system, the regulation of vasodilation and adrenaline levels, the release of endogenous opioids, and the increased anti-inflammatory cytokines. This article provided a clear explanation and summary of the research on exercise for complex regional pain syndrome. In the future, more high-quality studies with sufficient sample sizes may provide more exercise regimens and better evidence of efficacy.